2020
DOI: 10.20944/preprints202010.0551.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Non-Cannabinoid Metabolites of Cannabis sativa with Therapeutic Potential

Abstract: The Cannabis plant (Cannabis sativa L.) produces an estimated 545 chemical compounds of different biogenetic classes. In addition to economic value, many of these phytochemicals have medicinal and physiological activity. The plant is most popularly known for its two most prominent and most studied secondary metabolites— Δ9-Tetrahydrocannabinol (Δ9-THC) and Cannabidiol (CBD). Both Δ9-THC and CBD have a wide therapeutic window across many ailments and form part of a class of secondary metabolites called c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Lowe et al reported the potential of a cannabis-based flavonoid pharmaceutical composition containing cannflavins A, B, and C in addition to several other flavonoids to prevent and treat several central nervous system-linked diseases and disorders. 54 …”
Section: Biological Activities Of Cannflavinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowe et al reported the potential of a cannabis-based flavonoid pharmaceutical composition containing cannflavins A, B, and C in addition to several other flavonoids to prevent and treat several central nervous system-linked diseases and disorders. 54 …”
Section: Biological Activities Of Cannflavinsmentioning
confidence: 99%
“…As a part of the cannabis-based pharmaceutical composition, cannflavins A, B, and C exhibited prevention and treatment potential against several types of cancers targeting oncogenic factors, such as kinases, sirtuins, bromodomains, matrix metalloproteinases, and BCL-2. 57 …”
Section: Biological Activities Of Cannflavinsmentioning
confidence: 99%
“…Debido a que cuando una falla es severa, se generan altos costos de mantenimiento, ya sea por la salida de operación del proceso, daños a otros componentes, contaminación ambiental, etc. (Cardona, Batista, & Rodrı ǵuez, 2008) (Lowe, Toyang, & Bryant, 2018).…”
Section: Justificaciónunclassified